Uso de zeólitas como alternativa para minorar os efeitos do estresse salino em plantas de Ixora coccínea L. - Sousa, Humberto Gildo de (2019)
Horticultural production, especially ornamental production, is associated with high water consumption, thus requiring availability of fresh water to ensure satisfactory productivity so that it is acceptable in the flower market. The high water requirements by the crops or even the low quality of several water sources for irrigation, can favor the use of another source unsuitable for agriculture, as in the case of salt water and brackish water. However, this resource, once used in an uncontrolled way, can cause several problems related to soil structure and crop development. The objective of this research was to evaluate the tolerance of an ornamental plant species to four increasing levels of irrigation water salinity and the potential of a zeolite species to reduce the effects of saline stress. The research was carried out in a greenhouse at the Agrometeorological Station experimental area, belonging to the Agricultural Engineering Department, at the Pici Campus, Federal University of Ceará, Fortaleza - Ceará, from April to June 2018. A randomized complete block design (DBC) was used in a 4 × 2 factorial scheme, corresponding, four levels of irrigation water salinity (CEa) (0.6, 2.0, 3.4 and 5.0 dS m-¹), with presence and absence of zeolite, totaling 8 treatments, with 4 replicates. The treatments were distributed in randomized blocks in a factorial scheme with four replicates, each replicate with three plants and four saline levels, with presence and absence of zeolites. The NaCl, CaCl2.2H2O and MgCl2.6H2O salts were added to the well water, in the proportion equivalent to 7: 2: 1, following the relationship between CEa and its concentration (mmolc L-1 = EC x 10). Each block had 24 experimental units totaling 96 plants of the coconut Ixora species and were transplanted to plastic vessels, with a volume of 7 liters, filled with one layer of gravel (number 0), with substrate where the composition was soil , hawthorn and earthworm humus in the ratio of 6: 3: 1, respectively A zeolite type A was added to the substrate in a quantity of 40 g per vessel. The amount of water was applied in order to provide a free drainage through the holes located in the lower part of the vessels and thus avoid excessive accumulation of salts and water in the substrate. Once a week, after the beginning of the drainage, a leaching fraction of 15% was supplied. Weeds will be disposed of manually. The variables analyzed were; Plant height, stem diameter, leaf number, leaf area, biomass production, specific leaf area, absolute growth rate, relative growth rate, percentage of live plants at the end of the experiment, leachate analysis, substrate analysis, relative chlorophyll index and sensorial analysis. The salinity of the irrigation water presented deleterious effects to the ornamental species I. coccinea, provoking reductions in leaf gas exchange, flower production and plant growth. No interaction of Na + in leaf tissues was observed, suggesting that the negative effects of salinity were mainly associated with the osmotic component of saline stress. Interaction between salinity and zeolites was observed for aerial biomass production, total biomass, number of branches, specific leaf area and leaf area ratio. However, the low sodium accumulation in the leaves made it difficult to elucidate some beneficial effect of zeolite on I. coccinea under salt stress.